PENGARUH GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY DAN TAX MANAGEMENT TERHADAP AKTIVITAS OPERASIONAL DAN NILAI PERUSAHAAN DI SEKTOR PERTAMBANGAN INDONESIA - Sugiharti, Sugiharti; Widyastuti, Tri; Sumarno , Sumarno (Yayasan Nuraini Ibrahim Mandiri, 2024)
The phenomenon gap in this research is that theoretically using price to book value and operational activities proxied using debt to equity based on the theory that the movement of firm value will correspond to the movement of operational activities. However, during the period from 2020 to 2023, there was inconsistency between the movement of price to book value and debt to equity which tended to fluctuate. The objective of this study is to analyze the influence of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), and Tax Management on Operational Activities and Firm Value (An Empirical Study on State-Owned Mining Sector Companies Listed on the Indonesia Stock Exchange for the Period 2020-2023). The population used in this research is all financial data of state-owned mining sector companies during the period of 2020-2023 listed on the Indonesia Stock Exchange. The sample consists of 40 data points from 6 state-owned mining sector companies that have issued complete annual financial reports during the observation period. The analytical tool used is quantitative analysis method, specifically path analysis. Based on the research findings, GCG does not have a negative effect on company value, while CSR and Tax Management do not have a positive effect on company value. Operational activities do not mediate the negative influence of GCG and tax management on company value, whereas operational activities mediate the positive influence of CSR on company value.